Pengaruh Pelatihan Dan Komunikasi Interpersonal Terhadap Kinerja Pegawai Pada Pusat Pengembangan Kompetensi (Pusbangkom) Aparatur Perdagangan Kota Depok - Ratih Suharningsih; Syarifah Ida Farida (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to determine the effect of training and interpersonal communication on employee performance at the Depok City Trade Apparatus Competency Development Center (Pusbangkom), both partially and simultaneously. This study was conducted using quantitative methods with a sample size of 55 respondents. The data analysis techniques used were: validity test, reliability test, normality test, multicollinearity test, autocorrelation test, heteroscedasticity test, simple linear regression test, multiple linear regression test, correlation coefficient test, multiple correlation coefficient test, coefficient of determination analysis test, t-test, and f-test. The results showed that training had a positive and significant effect on performance, as indicated by the regression equation Y=14.361 + 0.616 X1. The correlation coefficient indicates a strong relationship of 0.664. The coefficient of determination of the training variable indicates that the contribution of Training to Performance is 44%. The t-test produces a calculated T value of 6.468 > T table 2.006 with a significance of 0.000 < 0.05. Interpersonal Communication also has a positive and significant effect on performance, as shown by the regression equation Y=15.752 + 0.584 X2. The correlation coefficient indicates a strong relationship of 0.668, and the coefficient of determination of the interpersonal communication variable indicates that Interpersonal Communication contributes 45% to Performance. The t-test produced a calculated T value of 6.541 > T table 2.006 with a significance of 0.000 < 0.05. Simultaneously, Training and Interpersonal Communication have a positive and significant effect on Employee Performance, as shown by the regression equation Y = 9.487 + 0.380X1 +0.367X2. The correlation coefficient indicates a strong relationship of 0.744. The simultaneous coefficient of determination indicates that the contribution of training and interpersonal communication is 55%. The F test produced a calculated F value of 32.185 > F table 3.18 with a significance of 0.000 < 0.05. Thus, it can be concluded that Training and Interpersonal Communication partially and simultaneously have a positive and significant effect on Employee Performance